PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Ricky Josafat; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research was to determine the effect of leverage, company size and other factors on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange by obtaining empirical evidence. The factors used as independent variables in this research are leverage, company size, capital intensity, profitability, audit committee, and sales growth which can influence the occurrence of tax avoidance as the dependent variable by using the Effective Tax Rate (ETR) measurement. The population used in this research are all manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The sample selection was carried out using a purposive sampling method with predetermined criteria and resulted in 58 companies with 174 data that met the criteria and could be used as research samples. Data analysis in this research used multiple regression methods with several tests. From the tests and analysis carried out, this research shows that leverage has a positive effect on tax avoidance because greater leverage will increase interest expense as a deductible expense thereby reducing the level of tax expense and profitability has a negative effect on tax avoidance because the amount of profitability illustrates the amount of company profits that increase tax expense while other factors, namely company size, capital intensity, audit committee, and sales growth have no effect on tax avoidance. Keywords : Tax avoidance, leverage, capital intensity, profitability